Investigation of the qualitative composition and quantitative content of flavonoids in the herbal antidiabetic collections № 3 and № 4 by the method of HPLC - A. O. Savych; S. M. Marchyshyn; L. O. Kravchuk (Zaporozhye State Medical University, 2020)
Pharmacotherapy of diabetes mellitus is an extremely important problem of medicine and pharmacy due to its deficient safety and imperfection in maintaining optimal glycemia, frequent changes of which lead to the development of diabetes angiopathies. Therefore, the optimization of existing treatments with herbal collections is appropriate because of their low toxicity and the complex effect of the number of biologically active substances on the pathogenesis of diabetes and its complications. The aim of the research was to determine the qualitative composition and quantitative content of flavonoids in the herbal antidiabetic collections № 3 and № 4. Materials and methods. The objects of the study were the herbal antidiabetic collection № 3, which consists of folium Urticae, radix Cichorii, fructus Rosae majalis, rhizoma Erytrigiae repens, radix Taraxaci officinale, and the herbal antidiabetic collection № 4, which consists of radix Arctii lappa, rhizoma Erytrigiae repens, styli cum stigmatis Zeae maydis, flores Helichrysi arenarium, fructus Rosae majalis. The qualitative composition and quantitative content of flavonoids were determined by the method of high-performance chromatography using liquid chromatograph Agilent Technologies 1200. Results. It was identified 6 flavonoid and it was established their quantitative content, among which the rutin (0.36 %), neohesperidin (0.31 %), luteolin (0.17 %), quercetin (0.05 %), isoquercetrin 0.04 % and naringenin 0.04 % in the herbal antidiabetic collection № 3. It was identified 4 flavonoid and it was established their quantitative content, among which luteolin (0.42 %), rutin (0.29 %), quercetin (0.63 %) and isoquercetrin (0.63 %) in the herbal antidiabetic collection № 4. Conclusions. For the first time, it was determined the qualitative composition and quantitative content of the main flavonoids in the herbal antidiabetic collections № 3 and № 4 by the method of high-performance liquid chromatography. The results of the study showed that the herbal antidiabetic collection № 3 contains 6 flavonoids with a predominance of rutin and neohesperidin, and the herbal antidiabetic collection № 4 - 4 flavonoids, among which luteolin, rutin, and quercetin predominate. This gives reason to conclude about the antidiabetic activity by the pathogenetic mechanism of influence, which indicates that the feasibility of further study of these collections as promising herbal remedies for the treatment and prevention of diabetes mellitus.